Sperm Kinematics of Pesisir Bull Thawed at Different Temperatures and Times - Hendri, Hendri; Jaswandi, Jaswandi; Indriastuti, Rhesti; Ananda, Ananda (Buletin Peternakan, 2024)
Pesisir bulls from West Sumatra, Indonesia, have the potential to be valuable meat producers due to their adaptability and unique characteristics, but reproductive challenges necessitate the use of artificial insemination (AI) technology. The success of AI relies on the quality of frozen semen, which is influenced by thawing conditions, making the evaluation of sperm kinematics through Computer-Assisted Sperm Analysis (CASA) crucial for a comprehensive assessment of sperm function. This research evaluated the kinematics of frozen semen spermatozoa from Pesisir bulls. Frozen semen samples (n = 20) were thawed at 37°C for 10, 20, and 30 s and at 25°C for 30, 45, and 60 s. Kinematic parameters were observed using a Computer-Assisted Sperm Analyzer (CASA), including total motility (M), progressive motility (PM), the velocity of the average path (VAP) (?m/sec), the velocity of curvilinear (VCL) (?m/sec), the velocity of straight line (VSL) (?m/sec), straightness (STR) (%), linearity (LIN) (%), wobble (WOB) (%), amplitude of lateral head displacement (ALH) (?m), and beat/cross-frequency (BCF) (Hz). Thawed frozen semen at a temperature of 37°C for 20 s significantly (p<0.05) increased M, PM, and ALH. Furthermore, thawed frozen semen at 37°C for all durations and at 25°C for 60 s showed better quality for VAP, VCL, and VSL (p<0.05). Meanwhile, thawed frozen semen at 25°C increased STR, LIN, and WOB. However, thawing temperature and duration had no significant effect on BCF. Correlation analysis conducted on semen thawed at a temperature of 37°C for 20 s found that VAP was correlated with VCL, VSL, and ALH, while semen thawed at a temperature of 25°C for 60 s found that VAP was correlated with VCL, VSL, STR, LIN, and ALH. Most kinematic parameters were significantly better in the thawing treatment at 37°C compared to 25°C, suggesting careful consideration